Understanding complementarities among different forms of innovation - Torres, Pedro (2019)
Purpose – This study aims to better understand complementarities-in-performance of three forms of innovation: product innovation, process innovation, and organizational innovation. Additionally, complementarities-in-use for product innovation are examined, considering an additional condition: manufacturing flexibility. Design/methodology/approach – Using data from 223 unlisted Portuguese industrial firms, and a fuzzy-set qualitative comparative analysis (fsQCA), different combinations of different forms of innovation were examined to identify complementarities-in-performance and complementarities-in-use. Findings – Though the configurational analysis a path to achieve high performance was uncovered, which includes the presence of both product and organizational innovation. The study also reveals that the joint absence of two conditions (from the three that were considered in the analysis) can lead to low performance. This result indicates that the relationships among the antecedent conditions are non-linear. The configurational analysis also shows that the combination of manufacturing flexibility with either process innovation or organizational innovation can lead to high product innovation. This result confirms that manufacturing flexibility is an important condition for product innovation. Research limitations/implications – The empirical evidence reported in this paper may be influenced by the definitions that were considered. Further conceptual and empirical research is encouraged to corroborate (or refute) or consolidate the findings presented herein. Moreover, although the obtained results present a high empirical coverage, other antecedent conditions beyond the scope of this study can also play an important role; for instance, marketing could influence innovation performance. Furthermore, radical innovation was not distinguished from incremental innovation when analyzing firm performance. Practical implications – This study provides some clues for policy-makers that aim to enhance firm performance through innovation. Managers should focus on both organizational and technological innovation, in particular product innovation, to improve firm performance. Moreover, they should be aware of the complementarities-in-use for product innovation. Considering the importance of developing product innovation to3 enhance performance, firms should promote high levels of product innovation. To achieve this outcome, manufacturing flexibility should be present. Originality/value – Focusing on a very complex and still under researched topic, this study contributes to the complementarities literature in several ways. This study employs a configurational approach to better understand complementarities and to integrate technological and organizational innovation. By taking this approach this study acknowledges the existence of non-linearity and identifies not only the strategies to achieve high performance, but also the configurations that lead to low performance.